2013
DOI: 10.1080/02757540.2013.817568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leaching from alkaline red mud on soil biota: modelling the conditions after the Hungarian red mud disaster

Abstract: A soil column experiment was set up to investigate the effect of red mud from Ajka (Hungary) on a typical soil profile from the concerned area. The chemical changes caused by the leachate of the red mud and the effects of these changes on living organisms were assessed. Ecotoxicological tests with Vibrio fischeri, Sinapis alba and Folsomia candida were performed and the number of aerobic heterotrophic microorganisms was determined. The total, plant available, exchangeable and water soluble fractions of Na, Mo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
2
21
0
2
Order By: Relevance
“…This finding substantiated the recommended remediation option in the area: excavation of the RM flooded soil together with the overlain RM layer and storing of the excavated red mud and soil mixture (RMSM) in Ajka behind the red mud storage area. Rékási et al, 2013 showed similar results in a soil column experiment using 10 cm Ajka RM overlaying soil from Ajka: the CFU increased in the overlain soil until the 2 nd month, but it decreased by the 4 th month. Klebercz et al, 2012 measured 10-100 times elevation of CFU in the contaminated sediment of the rivers affected by the Ajka RM spill compared to reference samples.…”
Section: Discussionsupporting
confidence: 64%
“…This finding substantiated the recommended remediation option in the area: excavation of the RM flooded soil together with the overlain RM layer and storing of the excavated red mud and soil mixture (RMSM) in Ajka behind the red mud storage area. Rékási et al, 2013 showed similar results in a soil column experiment using 10 cm Ajka RM overlaying soil from Ajka: the CFU increased in the overlain soil until the 2 nd month, but it decreased by the 4 th month. Klebercz et al, 2012 measured 10-100 times elevation of CFU in the contaminated sediment of the rivers affected by the Ajka RM spill compared to reference samples.…”
Section: Discussionsupporting
confidence: 64%
“…The Mo and Na contents in the aqua regia digest of the untreated soil (S) were significantly higher than in the reference soil (R) ( Table 1). This may be due to leaching of these metals into the soil from the red mud deposit on the soil surface (S), as observed also by Rékási et al [30], in a column experiment modelling the leaching into the soil of metals from a 10 cm red mud layer.…”
Section: Results and Discussion 31 Metal Content Of The Red Mud And mentioning
confidence: 57%
“…Rékási et al [30] observed an increase only in the water soluble Cu, Cr and Na concentrations and in the plantavailable (NH4-acetate + EDTA soluble) Cu, Pb, Na and Mo concentrations. The total amount of Zn in the reference soil (R) was higher than in the untreated soil (S), but this might be due to local differences in parent material.…”
Section: Results and Discussion 31 Metal Content Of The Red Mud And mentioning
confidence: 98%
See 2 more Smart Citations